Methods of molecular quantum mechanics : an introduction to electronic molecular structure - Magnasco, Valerio (Chichester, U.K. : Wiley, 2009)
This provides an advanced text introducing graduate students to the mathematical foundations of methods needed to do working applications in molecular quantum mechanics. It contains a consistent use of atomic units from the very beginning for simplifying mathematical formulae, and presents a unified presentation of basic elements of atomic and molecular interactions, with particular emphasis on practical use of second-order calculation techniques.
Principles -- Matrices -- Atomic Orbitals -- Variation Method -- Spin -- Antisymmetry of Many-Electron Wavefunctions -- Self-consistent-field Calculations and Model Hamiltonians -- Post-Hartree-Fock Methods -- Valence Bond Theory and the Chemical Bond -- Elements of Rayleigh-Schroedinger Perturbation Theory -- Atomic and Molecular Interactions -- Symmetry.
Includes bibliographical references and indexes.
Print version record.
Keywords: Quantum chemistry; Molecular structure; Electrons; Electrons; Molecular structure; Quantum chemistry; Quantum theory; Electronic books